O povoamento da terra bracarense durante o século X - Amaral, Luís Carlos (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
As from the final decades of the 9th century, with the installation of the Galician-Asturian counts in the lands situated between rivers Minho and Mondego, the process of territorial reorganisation was given a strong impulse. This movement accelerated the integration of the region into the area of the Asturian-Leonese monarchy and contributed to an appreciable human and material development of society in north-eastern Iberia. The gradual increase of written documents clearly illustrates the multiplication of populated places and gives sufficient evidence of the social dynamism of the Braga region. Thus, in the present study, is an attempt to characterize and explain the main features which dominated this process during the decisive 10th century.